Effects of protein level and methionine supplementation during the periparturient period of dairy cows - Cardoso, Fabiana de Freitas (2018)
Cows go through a significant negative protein balance during the first 30 days of lactation. Given the functional effects of amino acids (AA) on health and inflammation, especially in challenging periods such as around calving, higher levels of protein and specific AA may improve health and intake. The response of dairy cows to three protein supplementation strategies during the transition period and through the first 45 days in milk was evaluated. Forty-six cows were blocked based on parity (primiparous vs. multiparous) and date of calving and within each block were randomly assigned to one of three treatments: low protein (LP), high protein (HP) or high protein with inclusion of rumen protected methionine (HPM). Treatments were offered from day -21 to 45 days relative to calving. Pre- and post-partum diets were formulated to contain high metabolizable protein (MP) capacity, and HP and HPM presented higher MP balance compared to LP treatment. Thirty-nine cows completed the experiment. Cows fed HPM consumed 2.8 kg/d more DM than did cows on LP treatment during pre- partum. We found no differences on BW and BCS across treatments in pre- and post- partum. Cows fed HP produced 2.5 kg/d more milk during the first 45 days of lactation than cows fed LP, although it was not statistically significant. Addition of RPMet to the HP diet did not increase milk production. Greater protein supplementation (HPM) reduced milk/DMI, increased milk urea nitrogen, and tended to increase plasma urea nitrogen. There was a lower blood interleukin (IL) 1 concentration on the cows fed HPM compared to the diet LP.The lymphocyte concentration in the blood was higher in the treatment of low protein. However, blood concentrations of insulin, glucose, non-esterified fatty acid, creatinine, beta-hydroxybutyrate, calcium, IL10 and TNFα did not differ among treatments during the experimental period.